Tongan Ways of Talking - Taumoefolau, Melenaite (Waka Kuaka, 2013)
In this article I distinguish six different "ways of talking" (after Grace 1981, 1987) in Tongan: kingly, chiefly, polite, self-derogatory, everyday and abusive ways of talking. I address the problem of words being traditionally ascribed to three speech levels of king, chiefs and commoners by recognising the existence of ways of talking in which the three categories of words are re-distributed. Ways of talking are not just "lexical" but full expressive systems about conventionalised subject matters. They are linguistic resources to be selected for use depending on the speaker's purpose and the social context.